Impact of Gamification on Knowledge Acquisition - Nakiyemba, Serena (European Journal of Information and Knowledge Management, 2024)
Purpose: The general objective of the study was to examine the impact of gamification on knowledge acquisition. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to gamification on knowledge acquisition. Preliminary empirical review revealed that integrating gamification elements into educational platforms and training programs consistently led to improvements in knowledge acquisition across various contexts. Gamified learning environments effectively motivated learners, fostered engagement, and facilitated collaborative learning experiences. Findings emphasized the importance of aligning gamification strategies with instructional goals, considering learner preferences, and iterating design based on feedback. While the study highlighted the potential of gamification to enhance learning outcomes, further research is needed to explore optimal strategies and long-term effects. Overall, gamification emerged as a promising approach for promoting effective learning and skill development. Unique Contribution to Theory, Practice and Policy: The Self Determination theory, Cognitive Load theory and Constructivism theory may be used to anchor future studies on gamification of knowledge acquisition. The study provided several recommendations based on its findings. Firstly, it suggested integrating gamification elements into educational programs to enhance engagement and learning outcomes. Secondly, it recommended leveraging gamification for promoting active learning and problem-solving skills among learners. Thirdly, it advised organizations to invest in gamified training programs to improve knowledge acquisition and job performance among employees. Lastly, the study emphasized the importance of ongoing research to better understand the effectiveness of gamification in education and training contexts.